Intrasynovial Tendon Graft for Chronic Flexor Tendon Laceration of the Finger: A Case Report - Sasaki, Jun (Bentham Open, 2013)
We present the case of a patient with flexor digitorum profundus tendon laceration at the A2 pulley level caused by an injury to the base of the right ring finger by a knife. The patient was treated by flexor tendon reconstruction from the palm to the fingertip by using the left second toe flexor tendon as a graft, which improved the active range of motion. Further improvement was achieved by subsequent tenolysis, which eventually restored nearly normal function. Our experience with this case indicates that the intrasynovial tendon is a reasonable graft source for the synovial space in fingers and may enable restoration of excellent postoperative function.